A NOVEL APPROACH OPTIMIZATION RANKED SYMMETRIC SEARCH ENCRYPTION USING CLOUD SECURITY SERVERS (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In the track of recent decades there is an especially extensive change in the PC innovation which prompts to an uncountable number of information and data rising in and everywhere throughout the world. Because of this gigantic and colossal dump of information and in addition web information most well known web indexes are encountering a considerable measure of unimportant recovery of information. The major try of this proposed Improved Weis to distinguish a precise information pursuit furthermore to produce information that originates from anyplace. Moreover, the information itself might be too expensive to store on a solitary machine to such an extent that the PCs are entomb associated with each other by the enormous web stockpiling advances. This approach for the most part spotlights on plan of web crawlers and its foundation grave. Enhanced Micro apportioning is a modularized approach of distributed computing for the most part encircled to conquer the pitfalls in the conventional web index furthermore in control of vast data put away in a solitary PC. Optimization Ranked Symmetric Search Encryption is efficiency. From this time forward, the Search motor in cloud creates low-inactivity and the information emergence will expand the productivity in its enhanced pursuit and along these lines beats the customary methodologies.